Comparison of cladding shaped of Tm/Yb doped fiber laser for optimum lasing efficiency - Saidin, Norazlina; Zainal Abidin, Mohd. Shahnan; Ahmad Damanhuri, Siti Sarah; Halder, Abul Fazal Mohammed Yusuf; Paul, Mukul Chandra; Harun, Sulaiman Wadi; Das, Srijit; Pal, Mrinmay C.; Bhadra, Shyamal Kumar (IEEE Photonics Society, Malaysia Chapter., 2016)
A Tm3+/Yb3+ doped fiber laser (TYDFL) using two different types of cladding shapes fiber was demonstrated. The fiber consists of a fabricated D-shaped cladding and circular cladding fiber with a double clad structure. The difference in the ratio of ions concentration between doped ions for both fibers resulted in different lasing output performance. The ring cavity laser setup was used to observe the free running lasers using high-power multimode 931 nm pump sources. It is observed that the D-shaped fiber shows better performances in terms of ASE and lasing compared to a circular shape cladding fiber. The threshold and slope efficiency of a D-shaped fiber were observed to be 1.7 W and 0.82%, respectively.